The impact of education on the benefits of cognitive-behavioral therapy on improving the quality of life of patients after breast cancer treatment - Majcher, Magdalena; Majcher, Monika; Świercz, Kamila; Górska, Dominika; Karwańska, Aleksandra; Pikulicka, Agata; Sierpień, Małgorzata; Brzychczy, Piotr; Kulbat, Aleksandra; Kulbat, Mateusz (Journal of Education, Health and Sport, 2023)
Introduction: Treatment of breast cancer may be associated with the subsequent occurrence of many side effects, which may have a significant negative impact on the quality of life of patients after treatment. Such patients may experience bothersome menopausal symptoms, persistent pain, insomnia and depressed mood. The most common treatment to combat the above symptoms is pharmacotherapy, which in turn could also be associated with additional side effects. Cognitive-behavioral therapy can be an effective alternative to pharmacological treatment as well as an effective complementary treatment. Aim of the study: The aim of the study is to summarize the current state of knowledge on the impact of cognitive-behavioral therapy on improving quality of life of patients after breast cancer treatment. Material and methods: The literature available in the Pubmed database was reviewed using key phrases. Results: Cognitive-behavioral therapy used in patients after breast cancer treatment brings good results in combating symptoms such as anxiety, depression, menopausal symptoms, persistent, chronic pain or insomnia resulting from the above symptoms. With the above therapy, you can correct not only the severity, but above all the perception of all of the above-mentioned symptoms, which is of key importance in the context of maintaining the quality of life as before the start of treatment. Conclusion: The development of patient education on the benefits of using cognitive behavioral therapy as an adjuvant treatment after breast cancer treatment may have a beneficial effect on improving the quality of life in these patients.